Barriers to community participation in tourism development in island destination / Nor Azah Mustapha and Inoormaziah Azman - Mustapha, Nor Azah; Azman, Inoormaziah (UiTM Press, 2013)
Research on the concept of community participation in tourism de-velopment has begun in the developed world. It has proven that the application of this concept is facing with barriers in developing countries so do with the island destinations. Hence, this paper illus-trates the barriers of community participation in tourism develop-ment in Tioman Island, Malaysia. It is a quantitative study involved 345 local people in several villages located in the island. The find-ings indicate that there are internal (culture) and external barriers (operational and structural) which hinder community participation. On top of that, it is found that weather is an external barrier high-lighted by the community. As they are segregated in several villages and largely depends on water transports, weather condition influ-ences their movements to participate in tourism development at the island. The research limitations relate to the geography factors ap-ply to the island which differ from the main land. It concludes that the intention to change is not just on the parts of the local people. Other stakeholders also need to provide opportunities to encourage community participation in tourism development. It is suggested that this research can be done in other islands to gain better under-standing on community participation in island tourism development.